Analisis Kepuasan Mitra Driver Gojek Terhadap Aplikasi Gopartner Dengan Metode End User Compunting Satisfaction (EUCS) - Sulaiman, Hamdun; Kudiantoro Widianto; Priatno; Muhammad Rifqi Ahdan (Infotek: Jurnal Informatika dan Teknologi, 2024)
GoJek's GoPartner application has many obstacles so this application does not fully provide service satisfaction to driver partners. The problem is the high level of complaints from driver partners on the GoPartner application which has the potential to reduce the quality of delivery services. Based on concerns and facts in the field regarding the GoPartner Application, it is necessary to analyze the satisfaction of Gojek driver partners as an object to find out what factors influence user satisfaction. This research aims to analyze the satisfaction of Gojek driver partners with the GoPartner application. This research was conducted by taking a sample of 94 drivers in the Kebagusan and Jagakarsa areas. The research results show that all factors simultaneously have an influence on user satisfaction. However, in the results of this research, there are only 3 variables that show that accuracy, format and timelines have a significant effect on user satisfaction, therefore there is a need to improve and increase several factors that have not had a significant effect, namely the Content and Ease of use variables due to these factors. is very important in influencing the satisfaction of GoPartner application users, so that in the future Gojek driver partners can provide maximum service